Investigation of the Degradation Mechanism of SiC MOSFET Subjected to Multiple Stresses - Huifen Dong; Yunxia Wu; Chan Li; Hai Xu (Micromachines, 2023)
The performance requirements for power devices in airborne equipment are increasingly demanding, while environmental and working stresses are becoming more diverse. The degradation mechanisms of devices subjected to multiple stresses become more complex. Most proposed degradation mechanisms and models in current research only consider a single stress, making it difficult to describe the correlation between multiple stresses and the correlation of failures. Then, a multi-physical field coupling model based on COMSOL is proposed. The influence relationship between temperature, moisture, electrical load, and vibration during device operation is considered, and a three-dimensional finite element model is built to investigate the multi-stress degradation mechanism under multi-physical field coupling. The simulation results show that, compared with single-stress models, the proposed multi-stress coupled model can more accurately simulate the degradation process of SiC MOSFET. This provides references for improving the reliability design of power device packaging.